Memorial meeting Malcolm X (1990)
Programma: 23 februari muziek: El Amal, Mamio Krioro, P.I. Man & Memre Boekoe, 2 Tuff Cheryl & D-Rebels, Small Boys, The D.A.M.N., Quality Crew; theater: Frank Shepard, Paul Middellijn.